Contribution to knowledge of the water beetles (Coleoptera: Adephaga, Hydrophiloidea) of Iceland, with unexpected observations on teratology - Czesław Greń; Krzysztof Lubecki (Zenodo, 2019)
Based on our own, original, quite intensive fieldwork, which we carried out during a two-week entomological expedition to Iceland in 2018, we recorded 6 species of water beetle from 3 families; none were new for this country. This confirms the good state of knowledge of this country’s fauna and also the typical paucity of water beetle species in circumpolar regions. Some families of water beetles, the members of which are common both in Europe and North America (Noteridae, Hydrochidae, Hydraenidae, Spercheidae, Elmidae, Dryopidae) are not represented at all in the Icelandic fauna. An unexpected observation, discussed at length in this paper, is the unusually high percentage of water beetles exhibiting teratological changes (3.48% of all the specimens caught), although these abnormalities related mainly to the number and shape of the antennomeres. We describe and illustrate these malformations, pointing out the need for the causes of their high incidence in Iceland to be further elucidated (> 3% versus < 3‰ among water beetles from other areas with which we are familiar). We also comment on aspects of morphology and, based on our field observations, on the habitat requirements of selected species.